Implementation of Minimum Service Standards Human Immunodeficiency Virus in Bandar Lampung City - A, Alfajar; Caturiani, Susana Indriyati; Puspawati, Ani Agus; Sulistyowati, Rahayu (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
HIV prevention and treatment remain major public health challenges in Indonesia, particularly in achieving the global 95-95-95 targets and the â€œThree Zeroâ€ vision. In Bandar Lampung City, performance indicators still show a significant gap between targets and actual outcomes. This study aims to evaluate the implementation of Minimum Service Standards (SPM) for HIV services and identify factors influencing policy implementation using Jan Merseâ€™s framework (information, policy content, community support, and potential distribution). This research employed a descriptive qualitative approach grounded in post-positivism. Data were collected through in-depth interviews, observation, and documentation involving stakeholders from provincial and city health offices, community health centers (Puskesmas), and civil society organizations (CSOs). Data analysis followed the interactive model of Miles, Huberman, and Saldana, including data condensation, data display, and conclusion drawing. Data validity was ensured through triangulation, transferability, dependability, and confirmability. The findings reveal that HIV SPM implementation in Bandar Lampung is constrained by several factors. First, information dissemination is uneven, with CSOs often lacking understanding of policy substance due to informal communication channels and limited socialization. Second, policy content is insufficiently operationalized at the local level, with unclear technical guidelines and heavy reliance on donor funding. Third, community support is strong in outreach and case detection; however, CSOs remain marginal in formal planning and budgeting processes. Fourth, the distribution of resources and roles is structurally defined but uneven, with limited laboratory capacity, insufficient counselors, and weak institutionalization of coordination mechanisms. These challenges contribute to inconsistencies in service delivery and suboptimal achievement of HIV targets. The study confirms that gaps in communication, resource allocation, policy clarity, and coordination significantly affect policy implementation effectiveness. Strengthening institutional coordination, improving dissemination of policy substance, ensuring sustainable budget allocation, and integrating CSOs into formal governance structures are essential to enhance HIV service delivery